New encrusting tentaculitoids from the Silurian of Estonia and taxonomic status of Anticalyptraea Quenstedt, 1867. (3rd April 2022) - Zatoń, Michał; Vinn, Olev; Toom, Ursula; Słowiński, Jakub
ABSTRACT: A new genus and species of encrusting tentaculitoid, Lindstroemiella eichwaldi, from the Silurian (Ludfordian Stage, Ludlow) of Saaremaa Island in Estonia, is described. This tentaculitoid shares common structural features (inwardly directed pseudopunctae and vesicles) with Anticalyptraea, but differs from the latter in having a spirally coiled, microconchid-like shell with a variously oriented aperture, thin and sharp transverse ridges and lacking an inverted cone-like morphology. Unlike other tentaculitoids (microconchids, trypanoporids, cornulitids), these encrusters, unique with respect to morphology and shell structure, have so far not been taxonomically classified at the ordinal level. Now, taking into account that such tentaculitoids are taxonomically and morphologically more diverse than previously assumed, we propose to include them in a separate order Anticalyptraeida. Unlike microconchids and cornulitids, anticalyptraeids are the least studied group of tentaculitoids and thus poorly recognized. In part, this may be due to their misidentification with associated spirally coiled microconchids, to which anticalyptraeids are very similar at juvenile stages. http://www.zoobank.org/lsid:zoobank.org:act:C1E9D9A4-555E-4F5A-BEDC-8046CCA58BD9